2000
DOI: 10.2307/2656859
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and chloroplast DNA‐based phylogeny of Pelargonium (Geraniaceae)

Abstract: Overall phylogenetic relationships within the genus Pelargonium (Geraniaceae) were inferred based on DNA sequences from mitochondrial(mt)-encoded nad1 b/c exons and from chloroplast(cp)-encoded trnL (UAA) 5' exon-trnF (GAA) exon regions using two species of Geranium and Sarcocaulon vanderetiae as outgroups. The group II intron between nad1 exons b and c was found to be absent from the Pelargonium, Geranium, and Sarcocaulon sequences presented here as well as from Erodium, which is the first recorded loss of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…The rbcL cpDNA region and mtDNA nad1b/c exon of just a few representatives of the genus have been sequenced (Price and Palmer 1993, Bakker et al 2000a, Soltis et al 2000. These study showed that Monsonia and Sarcocaulon are either sister genera or congeneric and sister to the other three (or four) genera in the Geraniaceae.…”
mentioning
confidence: 93%
“…The rbcL cpDNA region and mtDNA nad1b/c exon of just a few representatives of the genus have been sequenced (Price and Palmer 1993, Bakker et al 2000a, Soltis et al 2000. These study showed that Monsonia and Sarcocaulon are either sister genera or congeneric and sister to the other three (or four) genera in the Geraniaceae.…”
mentioning
confidence: 93%
“…On the other hand, excluding P. karooicum from the analysis fixes P. transvaalense in a position sister to a (Subsucculentia(Ciconium)) clade with 69% jackknife support (not shown). Previously, we interpreted the observation that our P. karooicum material has a P. caylae-type chloroplast, a Subsucculentia-type mitochondrion as well as a Subsucculentia karyotype (x = 10) as indicative of chloroplast capture from P. caylae (Bakker & al., 2000b). However, low support values for the incongruent P. karooicum clades (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…-Congruence among phylogenies derived from the different genomes is generally high with only three well-supported incongruencies found between the cpDNA trnL-F and rDNA ITS phylogenies and one between the trnL-F and nad1 phylogeny (Bakker & al., 2000b). Given that 149 taxa are involved and that "paternal leakage" and biparental inheritance have been reported in some species of Pelargonium (Tilney-Bassett, 1963;Kuroiwa & al., 1993;Nagata & al., 1997), the apparent rarity of topological incongruencies is somewhat surprising.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations